Expression of genes related to quality of Longissimus dorsi muscle meat in Nellore (Bos indicus) and Canchim (5/8 Bos taurus×3/8 Bos indicus) cattle - Giusti, Juliana [UNESP]; Castan, Eduardo [UNESP]; Dal Pai, Maeli [UNESP]; Arrigoni, Mario de Beni [UNESP]; Rodrigues Baldin, Samira [UNESP]; De Oliveira, Henrique Nunes [UNESP] (Elsevier, 2013)
This study was performed to compare CAPN1, CAPN2, CAST, TG, DGAT1 and LEP gene expressions and correlate them with meat quality traits in two genetic groups (Nellore and Canchim) in order to assess their expression profile and use their expression profile as genetic markers. We analyzed 30 young bulls (1. year old), 15 of each genetic group. Samples of the Longissimus dorsi muscle were collected for analysis of: total lipids (TL) and meat tenderness measured as Warner-Bratzler shear force (SF) and myofibrillar fragmentation (MFI) at day of slaughter and 7. days of aging. Gene expression profiles were obtained via RT-qPCR. TL and MFI showed differences between breeds, higher MFI in Canchim and higher TL in Nellore. Calpains showed no differential expression between groups, as did DGAT1, TG, and LEP. CAST was expressed more in the Nellore cattle. The only significant within-breed correlation (0.79) between gene expression and meat traits was found for DGAT1 and MFI in Canchim breed. Although the number of animals used in this study was small, the results indicate that the increased expression of CAST in Nellore may reflect tougher meat, but the lack of correlations with the meat traits indicates it is not a promising genetic marker. © 2013 Elsevier Ltd.
Keywords: Fat; Proteolytic enzymes; RT-qPCR; Differential expressions; Expression profile; Gene expression profiles; Genetic markers; Longissimus dorsi; Proteolytic enzyme; Meats; Muscle; Polymerase chain reaction; Gene expression; animal; cattle; cross breeding; gene expression regulation; genetics; meat; physiology; skeletal muscle; standard; Animals; Cattle; Crosses, Genetic; Gene Expression Regulation; Meat; Muscle, Skeletal